2009
DOI: 10.1002/jsfa.3830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetic acid deamidation‐induced modification on functional and nutritional properties and conformation of wheat gluten

Abstract: The results show that low-concentration acetic acid can modify wheat gluten mainly by deamidation, resulting in deamidated wheat gluten with good functional and nutritional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 29 publications
(25 reference statements)
4
58
0
Order By: Relevance
“…FTIR spectra of samples were prepared according to the method reported by Liao, Liu et al [15]. Mixed 1 mg of the freezedried WG powder with 200 mg of solid KBr powder.…”
Section: Fourier Transform Infrared Spectra Analysismentioning
confidence: 99%
“…FTIR spectra of samples were prepared according to the method reported by Liao, Liu et al [15]. Mixed 1 mg of the freezedried WG powder with 200 mg of solid KBr powder.…”
Section: Fourier Transform Infrared Spectra Analysismentioning
confidence: 99%
“…This role of electrostatics to deamidationinduced disruption of protein structure was supported by further observations on wheat gluten: both acetic acid and HCl induced deamidation had substantial consequences for the secondary structure of wheat gluten. It was thus postulated that strong deamidation induced protein unfolding as a result of electrostatic repulsion (Liao et al, 2010). Acetic acid induced deamidation of wheat gluten was further found to inhibit SDS-stable aggregate formation whilst largely retaining its ability to form disulfide bonds (Liao et al, 2010).…”
Section: Deamidationmentioning
confidence: 99%
“…It was thus postulated that strong deamidation induced protein unfolding as a result of electrostatic repulsion (Liao et al, 2010). Acetic acid induced deamidation of wheat gluten was further found to inhibit SDS-stable aggregate formation whilst largely retaining its ability to form disulfide bonds (Liao et al, 2010). The rate of the deamidation reaction has been found to depend on primary sequence and pH under which the reaction takes place, but was independent of ionic strength for model peptides (Patel & Borchardt, 1990a, 1990bRobinson & Rudd, 1974;Tyler-Cross & Schirch, 1991), soy protein and egg white lysozyme (Zhang et al, 1993).…”
Section: Deamidationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, deamidation with hydrochloric acid leads to certain problems, such as uncontrollable hydrolysis, the production of potentially carcinogenic compounds, including mono-and dichloropropanols and monochloropropanediols, and the isomerisation of certain amino acids, that have remain unresolved (Nagodawithana, 1994). Several studies have investigated the use of acetic acid in deamidation of proteins (Aranyi & Hawrylewicz, 1972;Berti et al, 2007;Liao et al, 2009;Wu et al, 1976). These studies showed that acetic acid-induced deamidation of proteins could be an economic and efficient way to improve the solubility, foaming and emulsification properties of proteins.…”
Section: Introductionmentioning
confidence: 99%